The infallibility of Bhartrihari in asserting the freedom of the doer: कर्तुः स्वातन्त्र्यप्रतिपादने भर्तृहरेरनवद्यता - Guha, Sajan (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
In the conflict does, the word doer is accomplished by the suffix trich by the formula “nvultrichou”. In the case of the doer, Panini wrote the formula “independent doer”. In the formula, the independent becomes independent. Here independence exists in the accomplishment of action. Therefore, he who is completely independent in the accomplishment of action is independent. And he is the doer. There are two words in the word independent. and the self and the system. The primary meaning of the word tantra is taken. The word self means the soul. That is, the Self whose system or principal is independent. For example, he is an independent Brahmin. Here the freedom or independence of the Brahmin is understood. Patanjali, the chief of grammar, in his explanation of the Panini formula that there is no subordination to anyone, introduced it. Taking that view as his head, Bhartrihari has formulated six reasons for the freedom of the doer in the phraseology of the verse. Similarly, the first cause is the acquisition of power in the accomplishment of the principal action before the instinct of doing and other things by obtaining power from the preceding. The second reason for the freedom of the doer is that the actions and others are attained by autonomous transactions such as by attaining the nature of nyag. The third reason for the independence of the doer is that in the accomplishment of action, by the instinct under it, etc., the action and others are induced under themselves. Similarly, the fourth cause is the renunciation of the auxiliaries involved by the renunciation of the involved. The fifth cause is the doer’s willingness to see his own representative even in the absence of the representative goodness of the actions and others, since they are unseen. Again, in discrimination, by seeing, etc., in the absence of other factors, seeing oneself is the sixth cause in the independence of the doer. Thus, although the doer helps from afar in the accomplishment of the action when the other factors are interrupted, the six causes say that it is predominant in the main action when it is independent. But the independent noun of karana and others is not defined. Because even though they are independent in their own businesses, they are transcendental because they are subject to the doer in the main action. The freedom of the doer is defined according to the phrasal verb. The interpretation, however, is entirely intelligent. Such is the greatness of the interpretation that it proves the independence of the doer even of the unconscious. Thus, living up to the Mahabhashya on the freedom of the doer in the phraseology, what Bhartrihari said, what is the past freedom of the doer in the accomplishment of action, and what is the importance of interpretation in the freedom of the doer? Abstract in Sanskrit Language: करोतीति विग्रहे “ण्वुल्तृचौ” इति सूत्रेण तृच्-प्रत्ययविधानेन कर्तृशब्दस्य सिद्धिर्भवति। कर्तुः प्रसङ्गे पाणिनिना “स्वतन्त्रः कर्ता” इति सूत्रमेवोदलेखि। सूत्रे स्वतन्त्रो भवति स्वाधीनः। अत्र स्वाधीनता क्रियासिद्धौ विद्यते। अतः क्रियासिद्धौ यः सम्पूर्णतया स्वाधीनो भवति सैव स्वतन्त्रः। स च कर्ता। स्वतन्त्रशब्दे शव्दद्वयं विद्यते। स्व च तन्त्रं च। तन्त्रशब्दस्य प्राधान्योऽर्थो गृह्यते। स्व-शब्दस्य आत्माऽर्थः। अर्थादात्मा यस्य तन्त्रं प्रधानं वा स स्वतन्त्रः। यथा-स्वतन्त्रोऽसौ ब्राह्मणः। अत्र ब्राह्मणस्य स्वतन्त्रता स्वाधीनता वा एवावगम्यते। न कस्यापि अधीनता इति पाणिनेः सूत्रस्य व्याख्याकार्ये वैयाकरणशिरोमणिना पतञ्जलिना प्रण्यनायि। तन्मतं शिरोधार्य्य वाक्यपदीये पदकाण्डे साधनसमुद्देशे भर्तृहरिणा कर्तृस्वातन्त्र्यविषये हेतुषटकं न्यरूपि। तथा च प्रागन्यतः शक्तिलाभादित्यादिना करणादिप्रवृत्तेः प्रागेव प्रधानक्रियासिद्धौ शक्तेरर्जनमिति प्रथमहेतुः। न्यग्भावापादनादित्यादिना स्वायत्तव्यापारेण करणादीनां न्यगभावापादनमिति कर्तुः स्वातन्त्र्यविषये द्वितीयहेतुः। तदधीनप्रवृत्तित्वादित्यादिना क्रियासिद्धौ करणादीनां स्वस्याधीने प्रवर्तनमिति कर्तुः स्वातन्त्र्ये तृतीयहेतुः। तथा च प्रवृत्तानां निवर्तनादित्यादिना प्रवृत्तानां सहायकानां निवर्तनमिति चतुर्थहेतुः। अदृष्टत्वात्प्रतिनिधेरित्यादिना करणादीनां प्रतिनिधिसद्भावेऽपि स्वप्रतिनिधेरदर्शनञ्च कर्तुः स्वैरिणि पञ्चमहेतुः। पुनः प्रविवेके च दर्शनादित्यादिना कारकान्तराणामभावे स्वस्य दर्शनमिति कर्तुः स्वातन्त्र्ये षष्ठहेतुः। एवं यद्यपि कारकान्तराणां व्यवधाने सति क्रियासिद्धौ कर्ता दूरादेवोपकरोति तथापि हेतुषटकेन स्वातन्त्र्यत्वे सति मुख्यक्रियायां तस्य प्रधानत्वमुच्यते। न तु करणादीनां स्वतन्त्रसंज्ञा व्यपदिश्यते। यतोहि तेषां स्वव्यापारेषु स्वातन्त्र्यत्वेऽपि मुख्यक्रियायां कर्त्रधीनत्वात् पारतन्त्र्यमेव। वाक्यपदीयानुसारं कर्तुः स्वातन्त्र्यं विवक्षाकृतम्। विवक्षा तु सर्वथा बुद्धिकृता। विवक्षाया एतादृशं माहात्म्यं यत्तया अचेतनस्यापि कर्तुः स्वातन्त्र्यं सिद्धम्। एवं वाक्यपदीये कर्तृस्वातन्त्र्यविषये महाभाष्यमुपजीव्य किमुक्तवान् भर्तृहरिः, क्रियासिद्धौ कर्तुः किं भूतं स्वातन्त्र्यं विद्यते, कर्तुः स्वातन्त्र्ये विवक्षायाः माहात्म्यमपि कीदृशम् एतान् सर्वान् विषयान् उपस्थापयिष्यामि अग्रे मूलप्रबन्धे। Keywords: भर्तृहरिः, स्वतन्त्रः, कर्ता, हेतुषटकम्, प्रागन्यतः शक्तिलाभात्